2019
DOI: 10.4067/s0718-221x2019005000407
|View full text |Cite
|
Sign up to set email alerts
|

The quality comparison of particleboards produced from heartwood and sapwood of European larch

Abstract: In this paper, the impacts of heartwood and sapwood usage on the physical, mechanical, and surface properties and formaldehyde emission of particleboard are investigated. European Larch (Larix decidua) trees are chosen as a raw material. The logs are divided into three segments: sapwood, heartwood and total wood. The highest amounts of cellulose (51,54%), and hemicelluloses (22,24%) in the sapwood, followed by total wood, and the heartwood, respectively. However, the highest amount of lignin (30,54%) was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Average detection rates of ClPAHs (89.1%) and BrPAHs (82.7%) were higher than those in other foods (ClPAHs, 41.6%; BrPAHs, 38.4%). ,, In raw bonito, the median concentration ratio of parent PAHs to XPAHs (P/X) has been reported as 9.22; however, the P/X ratio in smoke-dried bonito was 1400. It is well-known that PAHs are produced during wood burning, but no such information on XPAHs is available. Bardak et al reported that cellulose, hemicellulose, and lignin account for over 93.1% of three types of wood. These compounds are a source of carbon for PAHs but not a halogen source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average detection rates of ClPAHs (89.1%) and BrPAHs (82.7%) were higher than those in other foods (ClPAHs, 41.6%; BrPAHs, 38.4%). ,, In raw bonito, the median concentration ratio of parent PAHs to XPAHs (P/X) has been reported as 9.22; however, the P/X ratio in smoke-dried bonito was 1400. It is well-known that PAHs are produced during wood burning, but no such information on XPAHs is available. Bardak et al reported that cellulose, hemicellulose, and lignin account for over 93.1% of three types of wood. These compounds are a source of carbon for PAHs but not a halogen source.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that PAHs are produced during wood burning, but no such information on XPAHs is available. 47−49 Bardak et al 50 reported that cellulose, hemicellulose, and lignin account for over 93.1% of three types of wood. These compounds are a source of carbon for PAHs but not a halogen source.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Unfortunately, the reports lack data on the conditions of particle shredding and their geometry. A complex analysis of the particles is justified since their properties determine the properties of the particleboards (Nemli et al 2007, Nazerian et al 2011, Azambuja et al 2018, Bardak et al 2019. The particles properties depend on the material characteristics and the conditions of shredding process (Hernández et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bardak et al [ 95 ] dealt with the effect of the utilization of sapwood and heartwood on the particleboard surface properties, mechanical and physical properties, and the formaldehyde emissions from particleboard. Trees of European Larch ( Larix decidua Mill.)…”
Section: Larch Speciesmentioning
confidence: 99%